2019
DOI: 10.1016/j.bjpt.2018.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Knee crepitus is not associated with the occurrence of total knee replacement in knee osteoarthritis – a longitudinal study with data from the Osteoarthritis Initiative

Abstract: Objective(s): To investigate whether the presence of knee crepitus is associated with the occurrence of total knee replacement (TKR), quality of life and deficits in physical function at long-term. Methods: Setting-This observational study uses longitudinal data (up to 4-year follow-up) from the Osteoarthritis Initiative (OAI). Participants-4566 participants. Main Outcome Measure(s)-Logistic regression models were used to test if baseline knee crepitus is associated with the occurrence of TKR. Linear mixed mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…However, at long term (4 years), the presence of knee crepitus was not associated with lower physical function nor poorer quality of life in individuals with knee OA. 19 Even so, it is important to note that in a specific subgroup with preexisting tibiofemoral radiographic OA and without frequent knee pain, self-reported crepitus was found to be a predictor of knee OA. 14 Further studies should investigate if there is a difference between self-reported crepitus and objective measures of crepitus as predictors of future knee OA.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, at long term (4 years), the presence of knee crepitus was not associated with lower physical function nor poorer quality of life in individuals with knee OA. 19 Even so, it is important to note that in a specific subgroup with preexisting tibiofemoral radiographic OA and without frequent knee pain, self-reported crepitus was found to be a predictor of knee OA. 14 Further studies should investigate if there is a difference between self-reported crepitus and objective measures of crepitus as predictors of future knee OA.…”
Section: Discussionmentioning
confidence: 97%
“…17,18 Commonly, people associate the presence of crepitus with the need of future total knee replacement, 22 however, Pazzinatto et al investigated a large cohort and did not find any association within a 3 years period. 19 According to previous research, 22 crepitus is poorly understood and affects negatively patient's beliefs, altering movement pattern in an attempt to not hear the noise and can be responsible for the lack of adherence to exercise therapy. 22…”
Section: Discussionmentioning
confidence: 99%
“…Eine Studie zeigte, dass Patient*innen auf ein hör- und spürbares Knacken im Patellofemoralgelenk mit negativen Emotionen und einem Vermeidungsverhalten reagierten 13 . Abgesehen von affektiven Reaktionen als Konsequenz auf ein Knieknacken (in Kombination mit Schmerz) fehlen jedoch Hinweise auf physische oder die Lebensqualität betreffende Einschränkungen oder gar auf die Notwendigkeit eines Gelenkersatzes als Folge jahrelangen Knieknackens 14 . Das oft mahnend angeführte regelmäßige Knöchelknacken der Finger scheint keine Schäden an den Gelenken zu verursachen 15 , 16 und nicht mit einem erhöhten Arthroserisiko assoziiert zu sein 17 , 18 .…”
Section: Patient*innentheorienunclassified
“…e inclusion criteria for the patients of this study were as follows: the patients or their family members were fully aware of the research process and signed the informed consent, the patients were diagnosed with KOA [8][9][10][11] by examination and had knee pain and other symptoms, the patients were treated by TKA, and the patients who were older than 45 years old.…”
Section: Inclusion Criteriamentioning
confidence: 99%